K128 ubiquitination constrains RAS activity by expanding its binding interface with GAP proteins - Magits, Wout; Steklov, Mikhail; Jang, Hyunbum; Sewduth, Raj N; Florentin, Amir; Lechat, Benoit; Sheryazdanova, Aidana; Zhang, Mingzhen; Simicek, Michal; Prag, Gali; Nussinov, Ruth; Sablina, Anna (The EMBO journal, 2024)
The RAS pathway is among the most frequently activated signaling nodes in cancer. However, the mechanisms that alter RAS activity in human pathologies are not entirely understood. The most prevalent post-translational modification within the GTPase core domain of NRAS and KRAS is ubiquitination at lysine 128 (K128), which is significantly decreased in cancer samples compared to normal tissue. Here, we found that K128 ubiquitination creates an additional binding interface for RAS GTPase-activating proteins (GAPs), NF1 and RASA1, thus increasing RAS binding to GAP proteins and promoting GAP-mediated GTP hydrolysis. Stimulation of cultured cancer cells with growth factors or cytokines transiently induces K128 ubiquitination and restricts the extent of wild-type RAS activation in a GAP-dependent manner. In KRAS mutant cells, K128 ubiquitination limits tumor growth by restricting RAL/ TBK1 signaling and negatively regulating the autocrine circuit induced by mutant KRAS. Reduction of K128 ubiquitination activates both wild-type and mutant RAS signaling and elicits a senescence-associated secretory phenotype, promoting RAS-driven pancreatic tumorigenesis.
Keywords: signální transdukce; lysin; Signal Transduction; Membrane Proteins; neurofibromin 1; Humans; ubikvitinace; Lysine; Protein Binding; protein-serin-threoninkinasy; ras Proteins; protein aktivující GTPasu p120; lidé; p120 GTPase Activating Protein; zvířata; myši; protoonkogenní proteiny p21(ras); Mice; Protein Serine-Threonine Kinases; GTP-fosfohydrolasy; Ubiquitination; Proto-Oncogene Proteins p21(ras); vazba proteinů; nádorové buněčné linie; Ras proteiny; membránové proteiny; Animals; Cell Line, Tumor; Neurofibromin 1; GTP Phosphohydrolases